Development of a composite score based on carbohydrate antigen 19-9 dynamics to predict survival in carbohydrate antigen 19-9-producing patients with pancreatic ductal adenocarcinoma after neoadjuvant treatment - Rompen, Ingmar F.; Sereni, Elisabetta; Habib, Joseph R.; Garnier, Jonathan; Galimberti, Veronica; Perez Rivera, Lucas R.; Vatti, Deepa; Lafaro, Kelly J.; Hewitt, D. Brock; Sacks, Greg D.; Burns, William R.; Cohen, Steven; et al. (JCO precision oncology, 2024)
Purpose - Dynamics of carbohydrate antigen 19-9 (CA19-9) often inform treatment decisions during and after neoadjuvant chemotherapy (NAT) of patients with pancreatic ductal adenocarcinoma (PDAC). However, considerable dispute persists regarding the clinical relevance of specific CA19-9 thresholds and dynamics. Therefore, we aimed to define optimal thresholds for CA19-9 values and create a biochemically driven composite score to predict survival in CA19-9-producing patients with PDAC after NAT. - Methods - Patients with PDAC who underwent NAT and surgical resection from 2012 to 2022 were retrospectively identified from three high-volume centers. CA19-9 nonproducers and patients with 90-day mortality, and macroscopically incomplete resections were excluded. A composite score was created on the basis of relative CA19-9 change and newly defined optimal thresholds of pre- and postneoadjuvant values for overall survival (OS) using patients from two centers and validated using data from the third center. - Results - A total of 492 patients met inclusion criteria in the development cohort. Optimal CA19-9 cutoff values for predicting a difference in OS were 202 U/mL for preneoadjuvant and 78 U/mL for postneoadjuvant levels. Furthermore, increase in CA19-9 during neoadjuvant treatment was associated with worse OS (median-OS, 17.5 months v 26.0 months; P = .008). Not surpassing any or only one of these thresholds (composite score of 0-1) was associated with improved OS compared with patients with 2-3 points (median-OS, 29.9 months v 15.8 months; P < .001). Major serological response (90% decrease of CA19-9) had a positive and negative predictive value of 32% and 88%, respectively. - Conclusion - The composite score consisting of CA19-9 levels at diagnosis, after neoadjuvant treatment, and its dynamics demonstrates prognostic discrimination between low and high scores. However, better predictive biomarkers are needed to facilitate treatment decisions during neoadjuvant treatment.
Gesehen am 19.08.2025